2017
DOI: 10.1103/physrevlett.118.230501
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Monogamy Relations for Einstein-Podolsky-Rosen Steering in Gaussian Cluster States

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. Understanding how quantum resources can be quantified and distributed over many parties has profound applications in quantum communication. As one of the most intriguing features of quan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 74 publications
(111 reference statements)
1
99
0
Order By: Relevance
“…In [3][4][5], the authors have shown that the xth power of the entanglement of formation (x ≥ √ 2) and the concurrence (x ≥ 2) satisfy multiqubit monogamy inequalities. Monogamy relations for quantum steering have also been demonstrated in [17][18][19][20][21]. Later, polygamy inequalities were proposed in terms of the αth (0 ≤ α ≤ 1) power of square of convex-roof extended negativity (SCREN) and the entanglement of assistance [14,22].…”
Section: Introductionmentioning
confidence: 99%
“…In [3][4][5], the authors have shown that the xth power of the entanglement of formation (x ≥ √ 2) and the concurrence (x ≥ 2) satisfy multiqubit monogamy inequalities. Monogamy relations for quantum steering have also been demonstrated in [17][18][19][20][21]. Later, polygamy inequalities were proposed in terms of the αth (0 ≤ α ≤ 1) power of square of convex-roof extended negativity (SCREN) and the entanglement of assistance [14,22].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the atomic or solid state-based encoding of continuous variable systems provide a novel method that can be used for quantum information processing. Based on the above two methods, various progress has thoroughly investigated the generation of bipartite or multipartite Gaussian steering, one-way Gaussian steering, [30][31][32] and the potential applications such as one-sided device-independent QKD, [16] and secure quantum teleportation. [20][21][22][23][24][25][26] Gaussian steering is the quantum steering for Gaussian states under Gaussian measurement.…”
Section: Introductionmentioning
confidence: 99%
“…[19,26]. There has also been recent work on quantification of steering [17,27,28], monogamy relations [29,30,31], and multipartite steering [18,32]. Recently it has been shown the existence of steering inequalities for NOON states [2].…”
Section: Introductionmentioning
confidence: 99%